Effects of selected pro-environmental projects in the regional development of Poland - Dembicka-Niemiec, Agnieszka (Oddziaływanie wybranych projektów prośrodowiskowych na rozwój regionów − przykład Polski, 2019)
Pursuant to the assumptions of the strategic document of the European Union, namely the Europe 2020 Strategy, objectives were designated for Member States in the scope of the conducted development policy. Poland is one of the beneficiaries of the Operational Programmes and receives financial support from the EU The main aim of the article is to verify whether the tasks implemented in that scope affect the development of particular regions. The objective of the article is the determination of the effect of pro-environmental projects on the development of Polish voivodeships. The analysis covered initiatives implemented in the scope of Operational Programmes in the programming period 2014-2020. Moreover, the levels of the development of Polish voivodeships in the selected years were determined by taxonomic research methods by Z. Hellwig, The analysis of changes in the development levels of voivodeships and pro-environmental projects in the area of which investments and activities concerning the low-emission economy, renewable energy sources, thermo-modernization and recycling are carried out is indicative of several conclusions. The low share of projects related to recycling and strictly environmental protection is worrying. In all voivodeships, most pro-environmental projects financed by ROP concern thermomodernization
Biblioteka Regionalisty, 2019, Nr 19, s. 20-36
Keywords: Dolny Śląsk